Cells at the center of dictyostelium aggregates become spores. - Huang, H; Takagawa, D; Weeks, G; Pears, C (Elsevier, 1997)
The cellular slime mold Dictyostelium discoideum undergoes a developmental life cycle on starvation to generate a fruiting body consisting of a mass of spores supported on a stalk of dead, vacuolated cells. The choice between alternative cell fates is influenced by a variety of factors including cell cycle position at the onset of starvation. We present evidence to suggest that the cell cycle position influences cell fate by determining the position of cells in the early aggregate. The existence of a strain which cannot initiate development on its own but which can respond to signals generated by nonmutant cells has allowed us to investigate the eventual cell fate of the initiating cells which are, by definition, at the center of the early aggregate. Cells which have a propensity to become prespore cells show an increased efficiency in initiating development of this strain. Labeling the initiating cells by the expression of green fluorescent protein reveals that these cells become spores. The higher levels of expression of genes characteristic of early development in cells with a prespore tendency are consistent with the earlier expression of the components of relay in prespore cells.